SELEKSI UMPAN DAN UKURAN MATA PANCING TEGAK (Selection on bait and hook number of vertical line) - Noor Azizah; Gondo Puspito (Bogor Agricultural University, 2012)
ABSTRACTExperimental research on vertical line using different bait and hook size to catch hairtail has been conducted in Palabuhanratu waters. Three kinds of bait were hairtails (Trichiurus sp.), sardine (Sardinella sp.), and mackerel (Rastrelliger sp.). Number of hooks consisted of 8, 9 and 10. All fishing operations were done on floating lift net. From the experiment, bait of sardine was more effective to catch hairtails of Trichiurus savala than hairtails and mackerel. The three baits cought 69, 54 and 46 hairtails of Trichiurus savala, respectively. While, bait of hairtails was more suitable to catch hairtails of Trichiurus haumela. Bait of hairtails, sardine and mackerel cought 11, 7 and 1 hairtails of Trichiurus haumela. Hook number 8 gave the greatest number of catch, i.e. 62 hairtails of Trichiurus savala and 11 hairtails of Trichiurus haumela.Keywords: Hairtails, vertical line, bait, hook number, and Palabuhanratu.——-ABSTRAKOperasi penangkapan layur dengan menggunakan jenis umpan dan ukuran mata pancing yang berbeda telah dilakukan di perairan Palabuhanratu. Jenis umpan yang dipakai adalah layur (Trichiurus sp.), tembang (Sardinella sp.), dan kembung (Rastrelliger sp.). Adapun ukuran mata pancing yang digunakan terdiri atas nomor 8, 9 dan 10. Operasi penangkapan dilakukan di atas bagan apung. Dari hasil penelitian didapatkan bahwa umpan tembang paling efektif untuk menangkap layur bedog (Trichiurus savala), selanjutnya layur dan kembung. Masing-masing menghasilkan 69; 54 dan 46 ekor. Adapun umpan layur lebih efektif untuk menangkap layur meleu (Trichiurus haumela) dibandingkan dengan tembang dan kembung. Masing-masing menangkap 11, 7 dan 1 ekor layur meleu. Mata pancing nomor 8 menghasilkan jumlah tangkapan layur bedog dan layur meleu terbanyak, yaitu 62 dan 11 ekor.Kata kunci: Layur, rawai tegak, umpan, nomor mata pancing dan Palabuhanratu